PERSAINGAN PENJUALAN BUKU PELAJARAN PADA PERUSAHAAN PENERBITAN BUKU DI KOTA JAMBI - Hafrianto Hafrianto; Nazori Majid; Addiarrahman Addiarrahman (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to provide an analysis of Textbook Sales Competition at a Book Publishing Company in Jambi City. This study is important to do in order to find out the causes, directors, and Business Ethics of book publishing companies in facing competition in Jambi City. The method used is a descriptive qualitative approach. Data collection techniques in the form of interviews, observations, and documentation. The results of this study, Marketing practices in book publishing companies in Jambi City may give rise to monopolistic practices that refer to unfair business competition that is prohibited in islam because it can disprove the competitors and harm to the consumers, which is certainly the opposite with sharia values. Whereas in Islam it has been arranged toin making peace always do good deeds and must not harm each other. Expected to book publishing companies applying the ethics of the right way of trading to the marketing is in accordance with Islamic sharia, one of which is with applying the five principles applied in Islamic business ethics in order to avoid monopolistic practices that refer to unfair business competition that is prohibited in islam.